(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
In the past decade, digital storytelling has gained recognition as an engaging and interactive instructional approach that can substantially improve English language acquisition, particularly in developing speaking abilities among EFL learners. Through the integration of multimedia tools with narrative expression, this method nurtures learners’ motivation, creativity, and communicative competence. The present paper examines the effective incorporation of digital storytelling in EFL contexts and its influence on learners’ oral fluency, motivation, and intercultural understanding.